Impact of underlying diseases and complications on COVID-19 mortality in South Korea: analysis of national health insurance service data - Kyunghee Lee; Jieun Hwang (Archives of Public Health)
Abstract Background Comorbidities or complications significantly influence coronavirus disease-2019 (COVID-19) severity and mortality risk. Therefore, this study aimed to compare treatment outcomes of COVID-19 inpatients by underlying diseases or complications. Method Data on COVID-19 patients from the National Health Insurance Service customized research database were analyzed while focusing on eight underlying diseases and complications: diabetes, hypertension, heart disease, kidney disease, liver disease, dementia, depression, and respiratory disease. Results Of the 377,812 COVID-19 patients in 2021, 51.47% were male and 48.53% were female, and post-diagnosis mortality was 2.04%; 68.7% (n = 259,560) of patients had at least one underlying condition, with the following frequency: respiratory disease (78.88%), heart disease (33.84%), hypertension (30.29%), liver disease (21.38%), depression (9.32%), kidney disease (4.89%), and dementia (3.87%). Among patients without any underlying diseases, 19.8% (n = 74,925) were treated for post-diagnosis complications, with the following frequency: respiratory disease (89.21%), liver disease (19.12%), heart disease (14.90%), diabetes (10.37%), hypertension (8.22%), depression (3.86%), kidney disease (2.04%), and dementia (0.64%). Except for liver disease, all underlying diseases were associated with mortality. COVID-19 patients with diabetes exhibited a 1.42-fold higher mortality risk (95% confidence interval [CI ]1.35–1.50). All complications were associated with death, with kidney-related complications conferring a 4.84-fold higher mortality risk (95% CI 3.62–6.48). Conclusion Underlying diseases and complications in COVID-19 patients were associated with death. Even with the same disease, the timing of onset, before or after COVID-19 diagnosis, induced a difference in the mortality risk. Both underlying diseases and complications should be considered for more proactive medical interventions.